المنحى الاستدلالي عند الإمام أبي الحسن الأشعري في المسائل العقديّة: An Analysis on the Issues of `Aqidah (Islamic Faith) Using Deductive Approach of al-Imam Abu al-Hasan al-Ash`ari - Maiga, Mohamed Hamdikinane (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
The present study aims to describe the deductive approach of al-Imam Abu al-Hasan al-Ash`ari in the issues of `aqidah (Islamic faith). Al-Ash`ari is widely considered a pioneer in the field of intellectual evidence (dalil `aqli) and transmittered evidence (dalil naqli) approaches. The strength of al-Ash`ari’s deductive approach is dependent upon two things: validity of the form of the argument and a strong type of evidence. Being himself as a recognized Islamic scholar, he based his arguments on Asma’ Allah (Names of Allah) Almighty. He did not think that analogical language measurement can penetrate strong arguments. Hence, the significance of this study lies in al-Ash`ari’s high intellectual power and his high quality knowledge. He has devoted the rest of his life to defend the teachings of the Qur’an and the Sunnah according to his logical compelling arguments. Therefore, the main objective of the study is to highlight al-Ash`ari’s method of reasoning and deduction in the issues of faith (`Aqidah), particularly to defend the beliefs of Ahl al-Sunnah wa al-Jama`ah. The study used the descriptive and analytical methods to explain the al-Ash`ari’s deductive approach. The study was first conducted by selecting al-Ash`ari’s texts for modeled reading and rearranged it according to the objectives of the study. Then, the author analyzed the selected texts to prove the relevance of deductive method used (a. his deductive method on the verses of al-Qur’an and the Sunnah; b. his analogical reasoning; c. inherent requirement for deductive method; d. highlight differences between issues). The findings show that al-Ash`ari does not only been successfully using his high intellectual power to meet the challenges on the issues of Islamic faith, but has also used his deductive arguments based on the verses of the Qur’an and the Sunnah. Further, these intellectual (`aqli) and transmitted (naqli) evidences are consistent with Islamic law. Finally, all these evidences are sufficient enough to demonstrate the power of God Almighty through His names and attributes and do not need to compare the attributes that exist in other creatures.